2012
DOI: 10.1016/j.labeco.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The determination of wages of newly hired employees: Survey evidence on internal versus external factors

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
0
28
1
Order By: Relevance
“…Similar empirical information is not available for Finland. Galuscak et al (2010) show, however, that the importance of external factors in hiring pay determination is quite strongly negatively correlated with union density and coverage. This implies that the wages of new employees should be more sensitive to external factors in Estonia than Finland.…”
Section: Structural Characteristics Of Our Three Economiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar empirical information is not available for Finland. Galuscak et al (2010) show, however, that the importance of external factors in hiring pay determination is quite strongly negatively correlated with union density and coverage. This implies that the wages of new employees should be more sensitive to external factors in Estonia than Finland.…”
Section: Structural Characteristics Of Our Three Economiesmentioning
confidence: 80%
“…The WDN survey findings about the main determinants of wages paid to newly hired employees provide indirect evidence on the relative flexibility of such wages across different countries. In this regard, Galuscak et al (2010) consider the share of firms that indicated that external factors -wages outside the firm or availability of workers in the market -are more important in determining the wages of the newly hired than factors internal to the firm, such as collective agreements or the pay of incumbent workers. The corresponding figures for Estonia and Spain imply that external labour market conditions are the dominant factor for a substantially larger share of firms in Estonia (32%)…”
Section: Structural Characteristics Of Our Three Economiesmentioning
confidence: 99%
“…If we instead turn to survey evidence, like Bewley (1999), Bewley (2007) for the U.S. and the study performed within the Eurosystem Wage Dynamics Network (WDN) covering about 17 000 firms in 17 European countries, we see strong evidence of that the wages of new hires are tightly linked to those of incumbents. As reported by Galuscak, Keeney, Nicolitsas, Smets, Strzelecki, and Vodopivec (2010), about 80% percent of the firms in the WDN survey respond that internal factors (like the internal pay structure) are more important in driving wages of new hires than external or market conditions. More direct evidence on the parameter we seek to calibrate is provided by Hall and Krueger (2008), who finds that between 25% and 50% of new hires receive posted wages and hence between 50% and 75% bargain over the wage.…”
Section: Calibrationmentioning
confidence: 96%
“…Using information from the second wave of the WDN survey, Galuscak et al (2010) report fairness considerations and the negative impact on morale as the main reasons preventing firms from deviating from the contract wage. On the other hand, labour regulations and collective agreements play a significant role in preventing firms from offering a lower wage to new hires.…”
Section: Theoretical Considerationsmentioning
confidence: 99%